A Theoretical and Empirical Approach to the Value of Information in Risky Markets: A Comment - Graham-Tomasi, Theodore (The Review of Economics and Statistics, 1988)
of Economics Departments, University of Westem Ontario Centre for Economic Analysis of Property Rights, Working Paper, 1986. Maddala, G. S., Limited-Dependent and Qualitative Variables in Economics (Cambridge: Cambridge University Press, 1983). McDowell, John M., and Michael Melvin, The Determinants of Co-Authorship: An Analysis of the Economics Literature, this REVIEW 65 (Feb. 1983), 155-160. McKelvey, R., and W. Zavoina, A Statistical Model for the Analysis of Ordinal Level Dependent Variables, Journal of Mathematical Sociology 4 (1975), 103-120. Schweser, Carl, The Economics of Academic Publishing, Journal of Economic Education 14 (1983), 60-64.